2015
DOI: 10.1039/c5an00968e
|View full text |Cite
|
Sign up to set email alerts
|

A label-free cyclic assembly of G-quadruplex nanowires for cascade amplification detection of T4 polynucleotide kinase activity and inhibition

Abstract: Several fluorescence methods have been developed for sensitive detection of PNK activity based on signal amplification techniques, but they need fluorescently labeled DNA probes and superabundant assistant enzymes. We have addressed these limitations and report here a label-free and enzyme-free amplification strategy for sensitively and specifically studying PNK activity and inhibition via hybridization chain reaction (HCR). First, the phosphorylation of hairpin DNA H1 by T4 PNK makes it be specifically digest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The IC 50 (half-maximal inhibitory concentration) curves of ADP and (NH 4 ) 2 SO 4 are shown in Figure . The IC 50 values for ADP and (NH 4 ) 2 SO 4 are 1.5 and 12.6 mM, respectively, which are comparable with the literature reported values. The result confirms that the paper-based fluorescence assay has the potential to screen PNK inhibitors as well as determine corresponding IC 50 values.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The IC 50 (half-maximal inhibitory concentration) curves of ADP and (NH 4 ) 2 SO 4 are shown in Figure . The IC 50 values for ADP and (NH 4 ) 2 SO 4 are 1.5 and 12.6 mM, respectively, which are comparable with the literature reported values. The result confirms that the paper-based fluorescence assay has the potential to screen PNK inhibitors as well as determine corresponding IC 50 values.…”
Section: Resultssupporting
confidence: 87%
“…The detection limit of PNK is 0.0001 U mL −1 according to the 3σ rule, which is lower than or comparative with those of previous reports (Table S1). [13][14][15][16][17][18][19][20]39,40 The assay−assay precision coefficient of variation (CV) of the PNK activity detection is below 5.1% in all experimental data sets, indicating that the assay has reasonable reproducibility. In addition, the detection principle is also demonstrated by gel electrophoresis analysis (Figure S6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, the signal change upon addition of T4 PNK was not the decisive factor due to its lesser contribution to S/B ratio (less than two times between the maximum and the minimum). Therefore, SA-6 with the lowest background had the best S/B ratio of 193, which is 1–2 orders of magnitude higher than S/Bs of other fluorescence methods. , As a consequence, our method exhibits substantial capability for a low limit of detection, and SA-6 was chosen for use in subsequent experiments.…”
Section: Resultsmentioning
confidence: 94%
“…T4 polynucleotide kinase (T4 PNK) is a functional enzyme that specifically acts in phosphorylation at the 5′-OH via the transfer of the γ-phosphate from ATP to DNA. This process plays a crucial part in DNA recombination and replication, as well as restoration. Many researchers have demonstrated that aberrant activity of T4 PNK, which induces abnormal phosphorylation, is related to some serious human diseases such as Rothmund–Thomson Syndrome, Werner Syndrome, and Bloom’s Syndrome. , Accordingly, it is of great importance to establish a highly sensitive detection strategy for T4 PNK, for use in inhibitor screening, clinical diagnostics, and drug discovery.…”
Section: Introductionmentioning
confidence: 99%